Field Experience Of Measuring The Acoustic Energy From A Hammer Blow To Coal Mine Roof And Its Relationship To Roof Stability - Peter Altounyan (International Conference on Ground Control in Mining, 2000)
The rate of decay of the energy from a hammer blow to a coal mine roof is related to the size and nature of the contacts between the rock being struck and its surroundings The use of this principle as a basis for testing roof condition in South African coal mines has been investigated under a SIMRAC funded project, with the objective of reducing the number of roof falls. ( I ) A prototype instrument having a simple numeric display related to the energy decay rate (the Acoustic Energy Meter) was constructed and used to carry out surveys at mines covering the range of coal mine roof geology and condition. The equipment was simple to use and provided excellent discrimination between visually intact roof and less stable conditions, once the normal/abnormal threshold had been established for a given site. Areas of potential roof failure were identified close to roof slips and igneous dykes, and confirmed in areas of visible deterioration. Directional stress effects on roof condition were also identified at some sites, with consistent differences in readings obtained depending on the direction of drivage. Repeat surveys also indicated areas where roof conditions were deteriorating with time. Based on the success of the prototype, a hand held version of the instrument. has been developed to a specification from Anglo Coal. This incorporates a simple 'traffic light' green / amber/ red display, making the device suitable for routine use by mine operatives This version is now undergoing trials at an Anglo Coal mine. It is concluded that the Acoustic Energy Meter shows great potential as a test instrument providing output which relates to the stability of the immediate roof.